2018
DOI: 10.1007/s11356-018-2665-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hepato-renal damage and genotoxicity induced by long-term exposure to five permitted food additives in rats

Abstract: The present study assessed the long-term daily administration of benzoic acid (BA), potassium sorbate (PS), chlorophyll (CPL), tartrazine (TAZ), and butylated hydroxyanisole (BHA) on hepato-renal changes and DNA damage in rats. Animals were orally administered with the 10 times of the acceptable daily intake (ADI) from each tested substance daily for 60 consecutive days. Blood, liver, and kidney samples were collected to evaluate hematological, biochemical, histopathological, and genotoxic alterations. The ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 29 publications
2
9
0
3
Order By: Relevance
“…Also, Chen et al [42] indicated that citric acid (as food additives) caused apoptotic DNA fragmentation in renal tissue of mice in a dose-dependent manner. Similar genotoxic findings were obtained by Abo-EL-Sooud et al [47] who displayed that rats orally administrated with Tz at dose of 3 mg/kg body weight, daily for 60 days, caused moderate to high degree of DNA damage in renal cells. Cur was also effective in reducing the apoptotic DNA fragmentation in renal cells of chick embryos in the current study.…”
Section: Discussionsupporting
confidence: 87%
“…Also, Chen et al [42] indicated that citric acid (as food additives) caused apoptotic DNA fragmentation in renal tissue of mice in a dose-dependent manner. Similar genotoxic findings were obtained by Abo-EL-Sooud et al [47] who displayed that rats orally administrated with Tz at dose of 3 mg/kg body weight, daily for 60 days, caused moderate to high degree of DNA damage in renal cells. Cur was also effective in reducing the apoptotic DNA fragmentation in renal cells of chick embryos in the current study.…”
Section: Discussionsupporting
confidence: 87%
“…The ingestion of this colorant has been associated to obsessive-compulsive disturbances and hyperactivity in children (Kamal and Fawzia 2018). Several studies have investigated the ability of tartrazine to interact with human serum proteins and cause damage on DNA (Leo et al 2018;Abo-EL-Sooud et al 2018). In recent studies, the administration of tartrazine with ADI levels in mice, showed an increase of lipid oxidation and alterations in biochemical markers in the brain tissue (Bhatt et al 2018), haematotoxin, immunotoxin effects, renal disorder, and increase of DNA abnormalities Abo-EL-Sooud et al 2018).…”
Section: The Class Of Colorants: Natural Vs Artificialmentioning
confidence: 99%
“…Several studies have investigated the ability of tartrazine to interact with human serum proteins and cause damage on DNA (Leo et al 2018;Abo-EL-Sooud et al 2018). In recent studies, the administration of tartrazine with ADI levels in mice, showed an increase of lipid oxidation and alterations in biochemical markers in the brain tissue (Bhatt et al 2018), haematotoxin, immunotoxin effects, renal disorder, and increase of DNA abnormalities Abo-EL-Sooud et al 2018). Sunset yellow, produced from aromatic compounds derived from petroleum, has also been associated with the increase of pro-inflammatory activity, as well as carmoisine, allura red, and ponceau 4 R, which are also reported to bind human and bovine serum albumin (Leo et al 2018).…”
Section: The Class Of Colorants: Natural Vs Artificialmentioning
confidence: 99%
“…Thus, the injection is more suitable for the cases of extreme VC deficiency and oral supplement could be more appropriate to chronic health disorders. Activities of ALT and AST are routinely measured as diagnostic tools in assessing hepatocellular injury (Abo-EL-Sooud et al, 2018;Abd-Elhakim et al, 2019;Behairy et al, 2020a). The significant increase in ALT and AST levels in BLD-injected rats in the current study is in agreement with the earlier findings of Neamat-Allah (2014) in veal calves.…”
Section: Discussionmentioning
confidence: 99%